2020
DOI: 10.3390/cli8030042
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Niche Models Reveal Climate Change Effect on Biogeographical Regions: The Iberian Peninsula as a Case Study

Abstract: How species are distributed on Earth depends largely on climate factors. Whenever these environmental conditions change, species tend to shift their distributions to reach more favourable conditions. Distinct sets of species similarly distributed (i.e., chorotypes) occur in biogeographical regions with homogeneous environmental conditions. Here, we analysed whether biogeographical regions are unstable over time (from the past to the future). We modelled the realised niche of amphibians and reptiles in the Iber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…We further observed that the distributional range of pancake tortoises would expand in the future (Fig 2; Table 1). The expansion of the future distributional ranges of reptiles has also been recorded by Houniet et al [55] for Bradypodion occidentale , González-Fernández et al [56] for Thamnophis melanogaster , Fathinia et al [57] for Pseudocerastes urarachnoides and Sousa-Guedes et al [58] for 13 different reptile species.…”
Section: Discussionmentioning
confidence: 61%
“…We further observed that the distributional range of pancake tortoises would expand in the future (Fig 2; Table 1). The expansion of the future distributional ranges of reptiles has also been recorded by Houniet et al [55] for Bradypodion occidentale , González-Fernández et al [56] for Thamnophis melanogaster , Fathinia et al [57] for Pseudocerastes urarachnoides and Sousa-Guedes et al [58] for 13 different reptile species.…”
Section: Discussionmentioning
confidence: 61%
“…We further predicted that the distributional range of pancake tortoises would expand in the future (Fig 2 and Table 1). The expansion of the future distributional ranges of reptiles has also been recorded by Houniet et al [69] for Bradypodion occidentale, González-Fernández et al [70] for Thamnophis melanogaster, Fathinia et al [71] for Pseudocerastes urarachnoides and Sousa-Guedes et al [72] for 13 different reptile species.…”
Section: Plos One Condition Has Been Reached (S1 Fig)mentioning
confidence: 62%
“…Generally, up to 13 species may lose their entire potential distribution by 2080 (Carvalho et al 2010). The Atlantic region will decrease in extent while the Mediterranean region will expand northwards (Sousa-Guedes et al 2020). These results are actually not surprising considering the hydric requirements of the studied species, as mentioned above (Carretero et al 2010;García-Muñoz and Carretero 2013;Rubio and Carrascal 1994); in fact, the highest among the lacertids studied to date (Garcia-Porta et al 2019).…”
Section: Discussionmentioning
confidence: 99%